PENGARUH MANAGEMENT CONTROL SYSTEMS TERHADAP FINANCIAL PERFORMANCE PERUSAHAAN MELALUI ORGANIZATIONAL CULTURE - Manuelita Nadia Isabell; Devie Devie Devie (Business Accounting Review, 2018)
This research study aimed to examine the affect of Management Control Systems in Financial Performance of registered manufacturing companies in Surabaya and its surroundings. This research used an intervening variable, Organizational Culture, which was hypothesized to strengthen the influence of Management Control Systems in the company's Financial Performance. Researchers used judgmental-purposive sampling technique as the basis for determining samples of the research. This research tested the samples of 33 registered manufacturing companies in Surabaya and its surroundings, covering 8 opened manufacturing companies (Tbk.) and 25 closed manufacturing companies (Non Tbk.) The research data processing was conducted using SmartPLS software. Management Control Systems was measured using four dimensions or indicators defined by Simons. Organizational Culture was measured using four dimensions or indicators defined by Cameron and Quinn. Financial Performance was measured using six financial indicators, namely Return on Assets (ROA), Return on Equity (ROE), Sales Growth, Profitability, Profit growth, and Market Growth. The results of research study indicated there was a positive and significant affect of Management Control Systems in the company's Financial Performance, a positive and significant affect of Management Control Systems in company’s Organizational Culture, and a positive and significant affect of Organizational Culture in the company's Financial Performance. The results of research study also indicated there was a positive and significant affect of Organizational Culture as an intervening variable which strengthened the affect of Management Control Systems in the company’s Financial Performance, although its influence as an intervening variable was found to be rather weak.